2023
DOI: 10.3390/cimb45030130
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Quantitative Proteomic Analysis during Different Stages of Somatic Embryogenesis in Larix olgensis

Abstract: Larix olgensis is an economically important tree species native to northeastern China. The use of somatic embryogenesis (SE) is efficient and enables the rapid production of varieties with desirable qualities. Here, isobaric labeling via tandem mass tags was used to conduct a large-scale quantitative proteomic analysis of proteins in three critically important stages of SE in L. olgensis: the primary embryogenic callus, the single embryo, and the cotyledon embryo. We identified 6269 proteins, including 176 sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Hesami and colleagues used transcriptome sequencing and identified 1,850 genes downregulated and 1,873 genes upregulated in embryogenic callus compared to non-embryogenic callus of cannabis [ 15 ], including 42 different TF classes (e.g., MYB, C2H2, ERF, AP2, bHLH, bZIP, B3, WRKY and GRAS ). Hou et al used LC-MS/MS (liquid chromatography with tandem mass spectrometry) and identified 6,269 differentially expressed proteins (DEPs) in three stages (the primary embryogenic callus, the single embryo, and the cotyledon embryo) of SE in Larix olgensis , including 18 TF families were identified, including 18 TFs from the AP2, NAM and WOX families [ 16 ]. Zhang et al identified 1,178 DEPs in the early SE of longan ( Dimocarpus longan ) and found that sodium butyrate (a deacetylase inhibitor) can reduce the proliferation and delay the differentiation of embryogenic callus by regulating the homeostasis of reactive oxygen species (ROS) andindole-3-acetic acid (IAA) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hesami and colleagues used transcriptome sequencing and identified 1,850 genes downregulated and 1,873 genes upregulated in embryogenic callus compared to non-embryogenic callus of cannabis [ 15 ], including 42 different TF classes (e.g., MYB, C2H2, ERF, AP2, bHLH, bZIP, B3, WRKY and GRAS ). Hou et al used LC-MS/MS (liquid chromatography with tandem mass spectrometry) and identified 6,269 differentially expressed proteins (DEPs) in three stages (the primary embryogenic callus, the single embryo, and the cotyledon embryo) of SE in Larix olgensis , including 18 TF families were identified, including 18 TFs from the AP2, NAM and WOX families [ 16 ]. Zhang et al identified 1,178 DEPs in the early SE of longan ( Dimocarpus longan ) and found that sodium butyrate (a deacetylase inhibitor) can reduce the proliferation and delay the differentiation of embryogenic callus by regulating the homeostasis of reactive oxygen species (ROS) andindole-3-acetic acid (IAA) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, up to date only a few studies have involved the proteomics of larch. For example, Zhang and collaborators used proteomics to study the mechanism of drought stress in Larix olgensis families [2]; Han and collaborators analyzed the formation of adventitious root development in hybrid larch with proteome [3]; and proteomics were widely used in the study of somatic embryogenesis in larch [4][5][6][7]. No studies to date have conducted a comprehensive analysis of the proteomic in needle senescence in L. gmelinii.…”
Section: Introductionmentioning
confidence: 99%